Implementation of Techno-Entrepreneurial Relationship Marketing (TERM) Model to Improve Competitiveness of Entrepreneurial Students in Central Java - Nugroho, Jati; Azizah, Azizah; Saptianing, Saptianing; Wahyuni, Sri; Astuti, Rif’ah Dwi; Nurkhayati, Isnaini; Fauziyyah, Alya Hasna; Slamet, Slamet (RSF Conference Series: Business, Management and Social Sciences, 2025)
To bridge the gap between entrepreneurial mindset and marketing effectiveness, thereby gaining a competitive edge, this study aims to develop and evaluate the Techno-Entrepreneurial Relationship Marketing (TERM) paradigm. This research investigates how techno-entrepreneurial relationship marketing, responsiveness capacity, and interaction proactiveness can help student entrepreneurs in Central Java improve their marketing performance. One hundred fifty business owners and managers from Central Java universities participated in this survey-based study. The research results confirm the important role of technology-entrepreneurship linkage marketing as a key mechanism linking strategic firm capabilities based on technology and entrepreneurship with superior market outcomes.